Physical activity and sedentary behaviour patterns in patients with knee osteoarthritis - Kaoje, Yusuf Suleiman (My University, 2017)
Objective: Physical activity (PA) is recommended in the management of osteoarthritis (OA) to reduce pain and improve function. Total volumes of PA and sedentary behaviour (SB) have been described in people with knee OA, but detailed information about the patterns of accumulation of PA and SB in knee OA populations is lacking. The purpose of this study was to objectively assess the patterns of accumulation of PA and SB and to explore associations with subjectively measured functional outcomes and quality of life in patients with knee OA. Methods: End-stage knee OA patients (n = 87, 65 ± 8.8 (mean ± SD) years, body mass index 34.4 ± 7.8 kg/m2) with Kellgren-Lawrence-defined grade 3-4 radiographic OA, wore an Actigraph and an activPAL accelerometer for 24 hours a day for 7 consecutive days. Total volumes of SB, light physical activity (LPA), moderate to vigorous physical activity (MVPA), and different bouts of SB, LPA, and MVPA were assessed. Self-report questionnaires were used to assess patient-experienced pain, function, quality of life and activities of daily living were the Western Ontario and McMaster Universities (WOMAC) osteoarthritis index and the Knee Injury Osteoarthritis Outcome Score (KOOS). Results: Of the 87 knee OA patients only 76 and 65 had complete Actigraph and activPAL data respectively. The participants had a mean (SD) age of 65.0 (8.8) years, were mostly women and most were classified as being obese with an average BMI of 34.4 (7.8) kg/m2. The Actigraph mean (95% CI) of awake wear time was 15.6 (15.1-16) hours/day, SB 10.9 (10.5-11.4) hours/day, LPA 4.5 (4.1-5) hours/day and MVPA 8.2 (3.3-13) min/day. Approximately 7% of patients met the current recommended PA guidelines. The activPAL mean (95% CI) of sitting time, standing time, stepping time and number of steps were 9.3 (8.5 – 10.1) hours per day, 5.0 (4.4 – 5.6) hour per day, 76.5 (66.6 – 86.3) minutes per day and 2489 (2130 – 2848) minutes per day respectively. There were variations in the hourly patterns of movement behaviours. Participants were significantly less sedentary between 6 am and 9 am compared to the grand mean of sedentary time per hour over the day (p<0.01) and were significantly more sedentary per hour from 3 pm to 7 pm (p<0.05). Significant correlations were found between WOMAC pain scores and Actigraph measured SB (r=0.277, p=0.031), LPA (r=-0.240, p=0.043), MVPA (r=-0.242. p=0.042), number of steps (r=-0.282, p=0.020), number of breaks in bouts of SB greater than 20 minutes (r=-0.292, x p=0.016), average duration of breaks in SB (r=-0.277, p=0.024), average duration of MVPA bouts (r=-0.326, p=0.012). Significant correlations were also found between WOMAC activity of daily living scores and Actigraph measured LPA (r=-0.206, p=0.048), MVPA (r=-0.246, p=0.029), number of steps (r=-0.286, p=0.010) and average duration of MVPA bouts (r=-0.383, p=0.002). Significant correlations were found between WOMAC pain scores and activPAL sitting time (r=0.029, p=0.02), and stepping time (r=-0.029, p=0.01), between self-reported WOMAC activity of daily living score and stepping time (r=-0.309, p=0.02), between KOOS activity of daily living score and stepping time (r=-0.276, p=0.004), and between KOOS quality of life score and stepping time (r=-0.263, p=0.008). Conclusion: This study describes novel detail of the patterns of activity and sedentary behaviour in patients with knee OA. The use of two accelerometers gives a detailed account of daily activity and the variation throughout the day, highlighting when interventions to improve activity might be most effective. Therefore, interventions should target the long bouts of inactivity in this population. Since even healthy populations of older adults struggle to meet current recommended PA guidelines, it may be important to shift attention from meeting recommendations of MVPA to creating feasible suggestions of doing more light activity and breaking more sedentary time in knee OA patients.
A dissertation submitted to the Faculty of Health Sciences, University of the Witwatersrand, in fulfilment of the requirements for the degree of Master of Science in Medicine, Johannesburg, 2017
Keywords: Osteoarthritis, Knee; Sedentary Behavior; Exercise; Quality of Life